2021
DOI: 10.1002/jsfa.11366
|View full text |Cite
|
Sign up to set email alerts
|

Optimized seeding rate and nitrogen topdressing ratio for simultaneous improvement of grain yield and bread‐making quality in bread wheat sown on different dates

Abstract: BACKGROUND: Sowing date, seeding rate, and nitrogen (N) topdressing ratio have strong effects on grain yield (GY) and breadmaking quality (BQ) in bread wheat. Simultaneous improvement in GY and BQ in bread wheat has long been a challenge due to the inverse relationship between GY and grain protein concentration (GPC). In this study, we investigated whether the GY and BQ of bread wheat sown on different dates could be improved simultaneously by optimizing the seeding rate and the N topdressing ratio.RESULTS: De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
1
6
1
Order By: Relevance
“…In the present study, we observed the improvement in the GY of current two soft wheat cultivars with a reduced N rate when the top-dressed N application ratio was adjusted from 30 to 50% at the jointing stage (Figure , Table and Supporting Information, Table S4). This agreed with the findings of Garrido-Lestache et al and Dong et al that enhancing a top-dressed N ratio could improve GY without changing the total N fertilizer application amount. Here, two-year field experiments confirmed that the combination of the reduced N rate with an enhanced top-dressed N ratio and increased plant density achieved both the required lower GPC for soft wheat and maintained a relatively higher GY, in relation to the conventional cultivation pattern (Figure , Table and Supporting Information, Table S4).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we observed the improvement in the GY of current two soft wheat cultivars with a reduced N rate when the top-dressed N application ratio was adjusted from 30 to 50% at the jointing stage (Figure , Table and Supporting Information, Table S4). This agreed with the findings of Garrido-Lestache et al and Dong et al that enhancing a top-dressed N ratio could improve GY without changing the total N fertilizer application amount. Here, two-year field experiments confirmed that the combination of the reduced N rate with an enhanced top-dressed N ratio and increased plant density achieved both the required lower GPC for soft wheat and maintained a relatively higher GY, in relation to the conventional cultivation pattern (Figure , Table and Supporting Information, Table S4).…”
Section: Discussionsupporting
confidence: 93%
“…Kajla et al ( 2015 ) also reported that high yielding varieties (PBW-343 and DBW-17) have flexibility, adaptability and well suited to timely as well as early sowing time. In another study from China, Dong et al ( 2022 ) found similar grain yield of wheat sown between 8 and 22 October but it decreased when sowing was delayed beyond 22 October. The effect of tillage was found non-significant and wheat yield was similar under CST (63.82 q ha − 1 ) and CT (63.99 q ha − 1 ) systems.…”
Section: Resultsmentioning
confidence: 96%
“…In the work of Zhang et al [119], the dough stability increased by 17% when sowing was delayed by 50 days. In turn, Dong et al [93] reported that early sowing, a high sowing density, and a high N rate applied in FN had a positive impact on dough stability. Contrary to Zhang et al [119] and the present study, Hao et al [111] and Soofizada et al [73] found that an increase in the sowing density had a negative effect on the dough stability.…”
Section: Rheological Properties Of Dough and Bread Qualitymentioning
confidence: 99%
“…There is also limited evidence to indicate that the sowing date is associated with the water absorption capacity of flour, dough stability, and bread loaf volume. Delayed sowing decreases the water absorption capacity of flour and dough stability and increases the bread loaf volume [92,93]. The optimal sowing density in wheat production also needs to be redefined due to global climate change.…”
Section: Introductionmentioning
confidence: 99%